Deciphering the exceptional kinetics of hierarchical nitrogen-doped carbon electrodes for high-performance vanadium redox flow batteries. Issue 10 (18th February 2022) - Li, Yang; Yang, Shida; Zhao, Yunhe; Mubarak, Nauman; Xu, Mengyang; Ihsan-Ul-Haq, Muhammad; Zhao, Tianshou; Chen, Qing; Kim, Jang-Kyo
Abstract : The exceptional kinetics of VO2 + /VO 2+ on a hierarchical nitrogen-doped carbon electrode are quantitatively deciphered by diffusion-less cyclic voltammetry and theoretical calculations. Abstract : High-performance vanadium redox flow batteries (VRFBs) necessitate robust carbon electrodes, whose rational design demands quantitative relationships between the electrode properties and performance. Here, we decipher the exceptional kinetics of VO2 + /VO 2+ on a hierarchical nitrogen-doped carbon (HNC) electrode. Diffusion-less cyclic voltammetry, a method developed to evade the complex influence of diffusion in three-dimensional porosity, quantifies a rate constant of ∼5 × 10 −7 cm s −1 on the electrode, substantially higher than that of un-doped porous carbons, in line with the calculated adsorption energies of solvated vanadium cations. The hierarchy is further linked to the high specific area via a comparison with graphite felt with and without carbon nanotube-decoration. The HNC electrode enables a VRFB of an exceptional energy efficiency of 76.8% over 2000 cycles at 400 mA cm −2, among the best reported. The work offers deep insights into the relationship of heteroatom doping, structural hierarchy, and kinetics for porous carbon electrodes for developing next-generation flow batteries.